Delta radiomic patterns on serial bi-parametric MRI are associated with pathologic upgrading in prostate cancer patients on active surveillance: preliminary findings - Midya, Abhishek; Hiremath, Amogh; Huber, Jacob; Sankar Viswanathan, Vidya; Omil-Lima, Danly; Mahran, Amr; Bittencourt, Leonardo K.; Harsha Tirumani, Sree; Ponsky, Lee; Shiradkar, Rakesh; Madabhushi, Anant (Frontiers in Oncology, 2023)
Objective: To quantify radiomic changes in prostate cancer (PCa) progression on serial MRI among patients on active surveillance and evaluate their association with pathologic progression on biopsy. Methods: This retrospective study comprised of N=121 biopsy proven PCa patients on AS at a single institution of which N=50 at baseline conformed to the inclusion criteria. ISUP Gleason Grade Groups (GGG) were obtained from 12-core TRUS guided systematic biopsies at baseline and follow-up. A biopsy upgrade (AS+) was defined as an increase in GGG (or in number of positive cores) and no upgrade (AS-) when GGG remained the same during a median period of 18 months. Of N=50 patients at baseline, N=30 had MRI scans available at follow-up (median interval=18 months) and were included for delta radiomic analysis. 252 radiomic features were extracted from the PCa region of interest identified by board certified radiologists on 3T bi-parametric MRI (T2-weighted (T2W) and apparent diffusion coefficient (ADC)). Delta radiomic features were computed as the difference of radiomic feature between baseline and follow up scans. Association of AS+ with age, prostate specific antigen (PSA), Prostate Imaging Reporting and Data System (PIRADS v2.1) score and tumor size were evaluated at baseline and follow-up. Various prediction models were built using random forest classifier (RF) within a 3-fold cross validation framework leveraging baseline radiomics (Cbr ), baseline radiomics+ baseline clinical(Cbrbcl ), delta radiomics (CΔr), delta radiomics+ baseline clinical(CΔrbcl), and delta radiomics+delta clinical (CΔrΔcl). Results: An AUC of 0.64±0.09 was obtained for Cbr which increased to 0.70±0.18 with integration of clinical variables (Cbrbcl ). CΔr yielded an AUC of = 0.74±0.15. Integrating delta radiomics with baseline clinical variables yielded an AUC of 0.77±0.23. CΔrΔcl resulted in the best AUC of 0.84±0.20 (p<0.05) among all combinations. Conclusion: Our preliminary findings suggest that delta radiomics were more strongly associated with upgrade events compared to PIRADS, and other clinical variables. Delta radiomics on serial MRI in combination with changes in clinical variables (PSA and tumor volume) between baseline and follow-up showed the strongest association with biopsy upgrade in PCa patients on AS. Further independent multi-site validation of these preliminary findings are warranted.